Design of Loading Test Rig used for Adjustable Gearbox based on LabVIEW - Wu Qianping; Li wei (Jixie chuandong)
According to the problem of the gearbox loading test rig can’t be automatically adjust,a method of three-dimensional adjustable structure improvement based on the cordwood is proposed,and the semi-automatic docking of different types of gearbox test is realized.At the same time,based on the NI 9232 dynamic signal acquisition module and using LabVIEW programming,the detection,data processing and related data storage of vibration signal in the gearbox running process are realized.Combining with the Modbus communication protocol based on LabVIEW,the programming of the control system of the loading test rig is carried out.